Integrated metabolomics and gut microbiota to reveal the anti-tumor mechanism of Jinfu’an decoction in tumor-bearing mice - Li, Peiqin; Peng, Huiting; Huang, Zhongming; Sun, Zhe; Li, Yantao; Wu, Siqi; Lin, Lin; Zhang, Shuqiao; Li, Hongyu; Cao, Yang (Frontiers in Microbiology, 2026)
IntroductionJinfu’an Decoction (JFAD), a traditional Chinese medicine, is used to treat lung cancer and has shown significant anti-tumor effects in clinical and experimental studies. This study integrates metabolomics and gut microbiota analysis to elucidate JFAD’s anti-tumor mechanisms.MethodsA suspension of A549-luc cells, approximately 1 × 106 in number, was injected subcutaneously into the right axilla of mice to establish a tumor-bearing nude mouse model. Mice were randomly assigned to four groups: model group (MG), low-dose JFAD (JFAD-L), medium-dose JFAD (JFAD-M), and high-dose JFAD (JFAD-H), receiving treatments via gavage for 21 days. Additionally, three nude mice formed the normal group (NG), receiving no treatment. Changes in gut microbiota and serum metabolites were assessed using 16S rRNA gene sequencing and UHPLC-QE-MS non-targeted metabolomics.ResultsJFAD may help restore the balance of intestinal flora in mice with lung cancer to a more normalized state. Our findings indicate that JFAD increases the abundance of Bacteroidia and decreases the presence of Firmicutes and Clostridia, thereby altering intestinal bacterial composition. Primary metabolic pathways associated with significant differences include nicotinate and nicotinamide metabolism, glycine, serine and threonine metabolism, and pyrimidine metabolism. A key differential metabolite identified was succinic acid, part of the central carbon metabolism pathway in cancer. Succinic acid showed a negative correlation with gut microbiota families Tannerellaceae and Campylobacterota. In the MG group, essential amino acid levels were markedly diminished but were significantly elevated after JFAD-M intervention. KEGG pathway analysis identified these amino acids as being linked to the PI3K/AKT and mTOR signaling pathways.DiscussionJFAD regulates the homeostasis of intestinal flora and influences amino acid and succinic acid metabolism through various pathways. These mechanisms could serve as potential targets for JFAD in inhibiting lung cancer invasion and metastasis.